Edible Filamentous Fungi from the Species Monascus: Early Traditional Fermentations, Modern Molecular Biology, and Future Genomics. Issue 5 (23rd June 2015) - Chen, Wanping; He, Yi; Zhou, Youxiang; Shao, Yanchun; Feng, Yanli; Li, Mu; Chen, Fusheng
Abstract Monascus spp. are filamentous fungi famous for their fermented products, especially red mold rice (RMR), a traditional fermented food in East Asian areas with a very long edible history documented back to the Han dynasty (BC 202‐AD 220) in China. Nowadays, RMR and its related products involve a very large industry from artisanal traditional fermentations to food companies to medicine manufacturers, which are distributed worldwide. Modern studies have shown that Monascus spp. are able to produce abundant beneficial secondary metabolites, such as monacolins (cholesterol‐lowering agents), γ‐amino butyric acid (an antihypertensive substance), dimerumic acid (an antioxidant), and pigments (food‐grade colorants), and some strains can also secrete citrinin, a nephrotoxic metabolite. Monascus‐related studies have received much attention because of their wide applications. However, to our knowledge, no systematic review on the progress of Monascus research has ever been published. In this review, the progress of research on Monascus is summarized into 3 stages: Monascus fermentation, Monascus molecular biology, and Monascus genomics. This review covers the past history, current status, and future direction of Monascus research, contributing to a comprehensive understanding of Monascus research progress.